PENERAPAN MODEL KURIKULUM TERPADU MATA PELAJARAN KKPI KOMPETENSI DASAR MENGOPERASIKAN SOFTWARE PENGOLAH KATA UNTUK MENINGKATKAN KETERAMPILAN MENULIS SURAT LAMARAN PEKERJAAN (Universitas Negeri Semarang, 2012)
Surat lamaran pekerjaan merupakan salah satu jenis surat yang perlu dikuasai oleh siswa SMK guna menghadapi dunia kerja. Keterampilan membuat surat lamaran pekerjaan, saat ini di SMK diajarkan pada mata pelajaran KKPI (Keterampilan Komputer dan Pengelolaan Informasi), Bahasa Indonesia dan Bahasa Inggris. Dua model kurikulum terpadu yaitu threaded dan connected mendorong peneliti untuk mendeskripsikan penerapan serta melihat seberapa peningkatan keterampilan siswa dalam menulis surat lamaran pekerjaan setelah penerapan model. Teknik pengumpulan data menggunakan teknik tes unjuk kerja, observasi dan wawancara. Pengolahan data dimulai dengan pengambilan data, reduksi data, paparan data, analisis data dan simpulan. Penerapan kurikulum terpadu baik threaded maupun connected dalam penerapannya mempunyai kesamaan dalam hal materi yang diajarkan, yaitu pengoperasian aplikasi pengolah kata dan surat lamaran pekerjaan berbahasa Indonesia dan berbahasa Inggris. Perbedaannya, kelas threaded diajarkan dengan team teaching oleh guru KKPI, Bahasa Indonesia dan bahasa Inggris sedangkan connected diajarkan oleh guru tunggal yaitu guru KKPI. Model kurikulum terpadu Threaded maupun Connected sama-sama menunjukkan peningkatan keterampilan menulis surat lamaran pekerjaan, meski demikian tidak terdapat perbedaan peningkatan yang signifikan antara keduanya. Threaded mempunyai kelebihan yaitu dengan team teaching yang terdiri atas beberapa guru menjadikan pengalaman dan pemahaman peserta didik lebih kaya. Kelebihan dalam pelaksanaan connected adalah guru dapat merancang skenario secara mandiri. Simpulan yang dapat ditarik adalah bahwa kedua model kurikulum terpadu ini dapat dijadikan salah satu alternatif model kurikulum terpadu khususnya dalam keterampilan menulis surat lamaran pekerjaan oleh guru-guru terkait di SMK. Job application letter is one of the letters that shall be mastered by vocational students for the preparation of entering work. Currently, the skill to write a job application letter is taught in the subject of KKPI (Computer and Information Processing Skill) relating to the application of data processing, meanwhile English and Indonesian are related to the content of the letter. Two models of integrated curriculum are threaded and connected to encourage researcher to describe the implementation and examine the improvement of student skill in writing the letter after using the model.The data were gathered using the techniques of work, observation and interview. Meanwhile the data were processed by collecting, reducing, describing, analyzing and summarizing them. Basically the implementation of threaded or connected cur-riculum has the similar aspects in terms of the material which uses word processing application (Ms. Word) and English or Indonesian job application letter. The dif ference between the curricula is the threaded curriculum taught by a team teaching of KKPI, English and Indonesian teachers but the connected curriculum is only taught by one teacher, KKPI.Threaded or Connected curriculum triggers the improvement of letter writing skill though there is only a slight dif ference. The advantage of threaded curriculum is upon the team teaching consisted of some teachers with some background and understanding that would benefit the students. On the other hand, if there is no coordination, the teacher will rely on each other so the basic competence would not be achieved due to lack of preparation to make a lesson plan. The advantage of connected curriculum is the independency of a teacher to make a lesson plan. In contract, it could be problematic if KKPI teacher does not master the material of writing an English and Indonesian job application letter so the lesson will only be dominated by KKPI subject.Regarding the advantages of integrated curriculum in KKPI with basic competence of operating data processing software with threaded as well as connected curriculum, vocational teacher shall implement both model especially in the competence of writing a job application letter. Some concerns that shall be taken into consid-eration are: concept understanding, types of model and steps of curriculum design by a need analysis.